Projectile Fragmentation of 16O and 32S beams from Dubna LHE Synchrophasotron - Sampsonidis, D.; Kulakov, B. A.; Krivopustov, M. I.; Butsev, V. S.; Zamani, M. (HNPS Advances in Nuclear Physics, 2020)
We investigate the charge changing collisions for 16O and 32S beams, using the experimental method of Solid State Nuclear Track Detectors (SSNTD). Sample reading was performed by an automatic measurement system. We determined the total charge changing cross sections and the partial cross sections for the production of fragments of cherge 9<Z<14.